ANALISIS KINERJA SEKTOR USAHA TANI PADI MELALUI PENDEKATAN AGRIBISNIS - Budi Santosa, Purbayu; Mohammad Khariza, Adhisty (Jurnal Organisasi Dan Manajemen, 2009)
This research is intended to describe the efficiency level of rice agriculture in Central Java. Agribusiness approaches enable to explain the agriculture sector more comprehensively, focusing on agriculture with its backward and forward subsystems. This research employs DEA (Data Envelopment Analysis) to compute efficiency level, and covers fourteen districts with land productivity above the province average level. This research finds that only four districts perform efficiency level 100 percent relative to other districts. The solution for this inefficiency problem can be achieved by employing managerial simulation generated by DEA.